Peningkatan Kemampuan Menyimak pada Pelajaran Bahasa Inggris dengan Metode Pembelajaran Kontekstual di Sekolah Dasar Kelas 2 - Nur Latifa (Pedagogia: Jurnal Ilmiah Pendidikan, 2016)
The aim of the research is to find out the application of contextual method to improve students’ listening skill in an English class. The subject of the research was second grade students, as many as 37 people. The research is a classroom action research using the model of Kemmis and Mc Taggart, conducted in two cycles. Each cycle consists of planning, implementation, observation, and reflection. The process of data collection was by listening test. Another instrument used was a non-test instrument which was the observational result of teaching using contextual method such as the observational sheets of the teacher and the students, notes, and documentation. The research result shows that there is improvement in students’ listening skill, in the aspects of conceptual, procedural, and problem solving with contextual method. It is proven by the average score of listening test in the first cycle which 64.86; it improved in the second cycle reaching 97.29. The activity of the teacher and the students are in accordance with the approach and they reached 100% at the end of the second cycle.